The Red Baron - Wright, Nicolas (New York : McGraw-Hill, 1977)
A biography of the World War I ace known as the Red Baron who shot down 80 Allied planes before he himself was killed, a month before his twenty-sixth birthday.
Includes index.
Keywords: Richthofen, Manfred, -- Freiherr von, -- 1892-1918.venile literature; Air pilots -- Germany -- Biography -- Juvenile literatur; World War, 1914-1918 -- Aerial operations, German -- Je; Air pilots.uvenile literature; World War, 1914-1918 -- Aerial operations, German